A simple technique for development of fibres with programmable microsphere concentration gradients for local protein delivery. Issue 4 (2nd January 2019) - Mehrpouya, Fahimeh; Yue, Zhilian; Romeo, Tony; Gorkin, Robert; Kapsa, Robert M. I.; Moulton, Simon E.; Wallace, Gordon G.
Abstract : Herein we present a simple approach for fabrication of alginate fibers with programmable microsphere concentration gradients for local protein delivery. Abstract : Alginate has been a biologically viable option for controlled local delivery of bioactive molecules in vitro and in vivo . Specific bioactive molecule release profiles are achieved often by controlling polymer composition/concentration, which also determines the modulus of hydrogels. This largely limits alginate-mediated bioactive molecule delivery to single-factors of uniform concentration applications, rather than applications that may require (multiple) bioactive molecules delivered at a concentration gradient for chemotactic purposes. Here we report a two-phase PLGA/alginate delivery system composed of protein-laden poly-d, l -lactic- co -glycolic acid (PLGA) microspheres wet-spun into alginate fibres. Fluorescein isothiocyanate-conjugated bovine serum albumin (FITC-BSA) was used as a model protein and the developed structures were characterized. The fabrication system devised was shown to produce wet-spun fibres with a protein concentration gradient (G-Alg/PLGA fibre). The two-phase delivery matrices display retarded FITC-BSA release in both initial and late stages compared to release from the PLGA microspheres or alginate fibre alone. In addition, incorporation of higher concentrations of protein-loaded PLGA microspheres increased protein release compared to the fibres with lower concentrations of BSA-loaded microspheres. The "programmable" microsphere concentration gradient fibre methodology presented here may enable development of novel alginate scaffolds with the ability to guide tissue regeneration through tightly-controlled release of one or more proteins in highly defined spatio-temporal configurations.